Assessing costs of carrying geolocators using feather corticosterone in two species of aerial insectivore. Issue 5 (May 2015) - Fairhurst, Graham D.; Berzins, Lisha L.; Bradley, David W.; Laughlin, Andrew J.; Romano, Andrea; Romano, Maria; Scandolara, Chiara; Ambrosini, Roberto; Dawson, Russell D.; Dunn, Peter O.; Hobson, Keith A.; Liechti, Felix; et al.
Abstract : Despite benefits of using light-sensitive geolocators to track animal movements and describe patterns of migratory connectivity, concerns have been raised about negative effects of these devices, particularly in small species of aerial insectivore. Geolocators may act as handicaps that increase energetic expenditure, which could explain reported effects of geolocators on survival. We tested this 'Energetic Expenditure Hypothesis' in 12 populations of tree swallows ( Tachycineta bicolor ) and barn swallows ( Hirundo rustica ) from North America and Europe, using measurements of corticosterone from feathers (CORTf ) grown after deployment of geolocators as a measure of physiology relevant to energetics. Contrary to predictions, neither among- (both species) nor within-individual (tree swallows only) levels of CORTf differed with respect to instrumentation. Thus, to the extent that CORTf reflects energetic expenditure, geolocators apparently were not a strong handicap for birds that returned post-deployment. While this physiological evidence suggests that information about migration obtained from returning geolocator-equipped swallows is unbiased with regard to levels of stress, we cannot discount the possibility that corticosterone played a role in reported effects of geolocators on survival in birds, and suggest that future studies relate corticosterone to antecedent factors, such as reproductive history, and to downstream fitness costs.